Бізнес-діагностика як інструмент пошуку проблем і визначення напрямів стратегічного розвитку компаній - Кривов’язюк, Ігор Володимирович (Одеса : Гельветика, 2025)
В статті розкрито роль бізнес-діагностики як сучасного інструменту пошуку проблем і визначення напрямів стратегічного розвитку компаній. Узагальнено підходи сучасних науковців до визначення сутності поняття “бізнес-діагностика” з подальшим формуванням власного трактування. Здійснено порівняльний аналіз традиційних і сучасних моделей бізнес-діагностики, що демонструє важливість побудови універсальних діагностичних систем, здатних не лише виявляти проблеми, а й трансформувати управлінське мислення на рівні стратегічного розвитку компаній. Розкрито взаємозв’язок бізнес-діагностики, її результатів і стратегічного розвитку компанії. За результатами досліджень шляхом логіко-структурного аналізу запропоновано напрями стратегічного розвитку компаній як особливу архітектурну платформу для формування варіативних сценаріїв розвитку, в межах яких можлива адаптивна перебудова бізнес-моделі компанії: через інновації, реструктуризацію, цифрову трансформацію, диверсифікацію або концентрацію.

The main goal of the study is to determine the role of business-diagnosis as modern instrument for searching problems and directions for strategic development of companies. The relevance of the topic is due to the importance of solving the issue of quick identification and solving problems of strategic development of companies. The methodological basis of the work is based on the system of applied research methods: theoretical generalization – to clarify the essence of the concept of “business diagnostic”; analytical – for comparative analysis of classic and modern models of business diagnostics; logical-structural analysis – when determining directions of strategic development of companies; specification and logical generalization – for formulating conclusions and developing recommendations based on research results. On the basis of critical analysis of the approaches of modern researchers to determine the essence of the concept of “business-diagnostic”, new term is proposed, which is identified with multifunctional management tool to merge the methods of financial, organizational, strategic and innovative analysis, ensuring comprehensive identification of problems and determination of directions for long-term development of companies. A comparative analysis of classical and modern models of business diagnostics emphasized the importance of building universal diagnostic systems capable not only of identifying problems, but also of transforming management thinking at the level of strategic development of companies. The interrelationship of business diagnostics, its results and the strategic development of the company presented in the work reveals the logic of integrating business diagnostics into strategic management as no longer an external tool, but as an internally mandatory stage of strategic decision-making logic. According to the results of research, through logical and structural analysis, directions of strategic development of companies are proposed as a special architectural platform for the formation of variable development scenarios, within which adaptive restructuring of the company's business model is possible: through innovation, restructuring, digital transformation, diversification or concentration.
Business diagnostics as a tool for searching problems and determining directions for strategic development of companies
Keywords: бізнес-діагностика; стратегічний розвиток; моделі бізнес-діагностики; цифрова трансформація; сценарії стратегічного розвитку; компанія